ENDORSING REFLECTIVE TECHNIQUES TO PROLIFERATE STUDENTS’ INTERACTIONS AND UTTERANCES IN A DISCUSSION FORUM - Marwito Wihadi (English Review: Journal of English Education, 2012)
Abstract: High Intermediate-2 studentsÃ¢â‚¬â„¢ brief responses in a discussion forum cause a long-expected discussion last in a couple of minutes in mixed-ability classes, depicting a minority of students are overtly dominant, while others are precisely passive. What yields discussions endure immaturely stems from both unclear roles of participants and their inadequate techniques to expand both interactions andÃ‚Â  spoken discourse. Therefore, Teacher-researcher assigned each participant in a discussion group of three to put reÃ¯Â¬â€šection into practice, referring to the self-selected and discussed topics. The data were gained through non-participant observations, in which the teacher-researcher observed and recorded a singled-out group. A sample recording was, subsequently, transcribed and analyzed regarding with the number of exchanges in a Ã¯Â¬Âve-minute discussion intake and the number of content words that students generated. It was found that employingÃ‚Â  reÃ¯Â¬â€šective techniques, students were able to keep a particular topic being discussed at full. As a result, the number of content words multiplied. These Ã¯Â¬Ândings resulted classroom teachers in insightful use ofÃ‚Â  reÃ¯Â¬â€šective techniques as one of the ways to proliferate studentsÃ¢â‚¬â„¢ beneÃ¯Â¬Âts in a discussion forum. Adequately practiced, students would be able to employ the techniques preponderantly,Ã‚Â  multiplying interactions among discussion members.Keywords:Ã‚Â  reÃ¯Â¬â€šective techniques, studentsÃ¢â‚¬â„¢ interactions, utterances, discussion forum.